Reducing the object orientation dependence of susceptibility effects in gradient echo MRI through quantitative susceptibility mapping - Li, Jianqi; Chang, Shixin; Liu, Tian; Wang, Qianfeng; Cui, Deqi; Chen, Xiaoyue; Jin, Moonsoo; Wang, Baocheng; Pei, Mengchao; Wisnieff, Cynthia; Spincemaille, Pascal; Zhang, Min; et al. (Magnetic resonance in medicine, 2012)
This study demonstrates the dependence of non‐local susceptibility effects on object orientation in gradient echo MRI and the reduction of non‐local effects by deconvolution using quantitative susceptibility mapping. Imaging experiments were performed on a 3T MRI system using a spoiled 3D multi‐echo GRE sequence on phantoms of known susceptibilities, and on human brains of healthy subjects and patients with intracerebral hemorrhages. Magnetic field measurements were determined from multiple echo phase data. To determine the quantitative susceptibility mapping, these field measurements were deconvolved through a dipole inversion kernel under a constraint of consistency with the magnitude images. Phantom and human data demonstrated that the hypointense region in GRE magnitude image corresponding to a susceptibility source increased in volume with TE and varied with the source orientation. The induced magnetic field extended beyond the susceptibility source and varied with its orientation. In quantitative susceptibility mapping, these blooming artifacts, including their dependence on object orientation, were reduced, and the material susceptibilities were quantified. Magn Reson Med, 2012. © 2012 Wiley Periodicals, Inc.